Incidence of retinal detachment after macular surgery: a retrospective study of 634 cases. Issue 10 (23rd May 2007) - Guillaubey, Alexandre; Malvitte, Laure; Lafontaine, Pierre Olivier; Hubert, Isabelle; Bron, Alain; Berrod, Jean Paul; Creuzot-Garcher, Catherine
Abstract : Aims: To evaluate the rate of retinal detachment after macular surgery. Methods: A retrospective non-randomised study of 634 macular surgery procedures was undertaken in two academic centres. Idiopathic macular hole (IMH) surgery (n = 272) and epiretinal membrane (ERM) surgery (n = 362) were performed between 2000 and 2003. We noted the anatomical and functional results of these procedures and we studied serious complications excluding cataract. Results: Minimum follow up was 1 year. No retinal detachment (RD) occurred in patients presenting with an intraoperative or preoperative successfully treated retinal break (RB). The rate of RD occurring after IMH surgery was higher than after the ERM surgical procedure (6.6% vs 2.5%, p = 0.02). The rate of RD was higher in patients presenting with stage 2 and 3 IMH than with stage 4 IMH. However, lens status as well as preoperatively treated RD did not influence the rate of RD after macular surgery. Conclusion: Retinal detachment remains the most common serious complication of macular surgery. Surgical detachment of the posterior vitreous face and associated peripheral retina anomaly seem to increase the rate of this complication. Careful examination of the peripheral retina is a key issue in preventing retinal detachment occurring after macular surgery.